Penerapan Metode WASPAS Dalam Penempatan Hawker Branded Dunhill Filter - Tiambun Romauli Silalahi; Abdul Sani Sembiring; Sumiaty Adelina Hutabarat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The location placement is an explanation related to the spatial layout of an economic activity, and this is always linked to the geographical allocation of limited resources which in turn will have an effect on and have an impact on both economic and social locations. Placement of location is a strategic activity that aims to maximize profits for the company. Placement of location greatly influences costs and determines income, location completely has the power to make or break a company's business strategy. To determine the recommendation for the placement of hawker brended dunhill filters at PT. Bentoel Group Asmo Medan can use the weight aggregated sum product assessment (WASPAS) method. The Waspas method can be used to rank the Hawkwer Dunhill Filter location with predetermined criteria.